An Empirical Study on Stress Modalities in IT Sector with Special Reference to COVID 19 (Journal of Pharmaceutical Negative Results, 2022)
This paper majorly signifies in handling of stress of an individual more emphasized on their cognition mishandled due to external environmental changes and relative compulsive forces acting especially in the context of COVID “19 who are Working from Home rather than working from MNC’s. In addition, it describes how to handle invidually to get motivated for generating the effective outcomes as on whole productively helpful for an organization. The employees working in different organizations have to deal with the stress. Especially IT professionals are under a great deal of stress due to many reasons. The stress contributes to decreased organizational performance, decreased employee overall performance, decreased quality of work, high attrition rate. Right at this point of time there is no way out to make the industry stress free. With increasing application of technology and new age facilities this kind of pressure is bound to increase. So, the sector has decided to face the problem rather than avoid it. Thus, this paper emphasis on the comparative study of stress impact on their performance work from Home and MNC’s Environment Due to COVID “19.